Physiological and Pathophysiological Insights of Nav1.4 and Nav1.5 Comparison - Loussouarn, Gildas; Sternberg, Damien; Nicole, Sophie; Marionneau, Céline; Le Bouffant, Francoise; Toumaniantz, Gilles; Barc, Julien; Malak, Olfat A.; Fressart, Véronique; Péréon, Yann; Baró, Isabelle; Charpentier, Flavien (Frontiers in Pharmacology, 2016)
Mutations in Nav1.4 and Nav1.5 α-subunits have been associated with muscular and cardiac channelopathies, respectively. Despite intense research on the structure and function of these channels, a lot of information is still missing to delineate the various physiological and pathophysiological processes underlying their activity at the molecular level. Nav1.4 and Nav1.5 sequences are similar, suggesting structural and functional homologies between the two orthologous channels. This also suggests that any characteristics described for one channel subunit may shed light on the properties of the counterpart channel subunit. In this review article, after a brief clinical description of the muscular and cardiac channelopathies related to Nav1.4 and Nav1.5 mutations, respectively, we compare the knowledge accumulated in different aspects of the expression and function of Nav1.4 and Nav1.5 α-subunits: the regulation of the two encoding genes (SCN4A and SCN5A), the associated/regulatory proteins and at last, the functional effect of the same missense mutations detected in Nav1.4 and Nav1.5. First, it appears that more is known on Nav1.5 expression and accessory proteins. Because of the high homologies of Nav1.5 binding sites and equivalent Nav1.4 sites, Nav1.5-related results may guide future investigations on Nav1.4. Second, the analysis of the same missense mutations in Nav1.4 and Nav1.5 revealed intriguing similarities regarding their effects on membrane excitability and alteration in channel biophysics. We believe that such comparison may bring new cues to the physiopathology of cardiac and muscular diseases.